2005
DOI: 10.1111/j.1467-9361.2005.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality in Rural China: Regression‐based Decomposition Using Household Data

Abstract: A considerable literature exists on the measurement of income inequality in China and its increasing trend. Much less is known, however, about the driving forces of this trend and their quantitative contributions. Conventional decompositions, by factor components or by population subgroups, only provide limited information on the determinants of income inequality. This paper represents an early attempt to apply the regression-based decomposition framework to the study of inequality accounting in rural China, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 27 publications
4
109
0
6
Order By: Relevance
“…45 China in the reform era has experienced not only extraordinary economic growth, but also dramatic increases in income inequality, especially for the least developed rural areas. [46][47][48][49] Whereas these changes have not adversely affected socio-economic disparities in maternal mortality between rich and poor counties over time, concerns remain over the health of vulnerable subgroups-particularly poorer rural communities and urban migrants-and the escalation in unnecessary, expensive and potentially harmful practices. Other emerging economies can learn from China's focus on the supply, funding and quality of maternity services, through a mix of specific and related maternal and child health policies and regulations, along with more general health-systems strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…45 China in the reform era has experienced not only extraordinary economic growth, but also dramatic increases in income inequality, especially for the least developed rural areas. [46][47][48][49] Whereas these changes have not adversely affected socio-economic disparities in maternal mortality between rich and poor counties over time, concerns remain over the health of vulnerable subgroups-particularly poorer rural communities and urban migrants-and the escalation in unnecessary, expensive and potentially harmful practices. Other emerging economies can learn from China's focus on the supply, funding and quality of maternity services, through a mix of specific and related maternal and child health policies and regulations, along with more general health-systems strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Using a decomposition of the Theil Index, Fan and Sun (2008) have identified that interregional inequality has been the driving factor in interprovincial income inequality during the 1990s. Other scholars have examined the role of various factors in contributing to regional variations in income inequality in China including the roles of capital investments (Tsui, 2007;Wan and Zhou, 2005) and policy (Fan, 1995). In recent years central government policy has emphasized developing the Western region and revitalizing the Central region of China (Goodman, 2004) to reduce income inequalities.…”
Section: Regional Inequality In Chinamentioning
confidence: 99%
“…6 In the following econometric analysis we use a wide set of household, household business and spatial factors. The selection of explanatory variables relies mainly on previous work on income mobility (Baulch & Hoddinott, 2000), determinants of poverty in the Chinese context (Wan & Zhou, 2005;Jalan & Ravallion, 2002) and theoretical work on poverty determinants (Callens, Croux, & Avramov, 2004) 7 . Household characteristics include household size, household head's age, educational attainments of the several household members, share of non-working population, household registration status and engagement in local administration.…”
Section: Table 1 Around Herementioning
confidence: 99%